“Wer heisst euch mit Fingern zeigen auf mich?”: Selbstreflexive Illusionsbrüche bei Hans Christian Andersen und Robert Schumann - Michaelsen, René (Danish Yearbook of Musicology, 2008)
The text takes a closer look at the relationship between Robert Schumann und Hans Christian Andersen – two artists of the mid-nineteenth century, who shared mutual admiration for each other. After summarizing how Schumann and Andersen got in contact through letters in 1842 and finally met in 1844, the article seeks to pin down structural relations between Andersen’s texts and Schumann’s compositional practice. Starting with a close examination of Andersen’s poem Der Spielmann and the special way Schumann set it to music in his Five Songs op. 40, and continuing with a comparison of techniques of framing in Andersen’s fairy tales as well as Schumanns Märchenbilder op. 113, it turns out that both the composer and the writer share a common goal: the exposition of an aesthetic illusion through activation of the reader-listener’s awareness of its modes of construction within the work. Taking its clues from textual procedures in Andersen’s work and the way Schumann deals with them in his compositions, the article also argues for genuine modes of musical self-reflexivity.